Hemorrhagic bronchial mucosa syndrome - Amit Panjwani (SpringerOpen, 2015)
Flexible fiberoptic bronchoscopy is a commonly performed procedure that helps in the management of pulmonary disorders. Complications during this procedure are uncommon. An elderly man was subjected to fiberoptic bronchoscopy for the evaluation of his respiratory disorder. He had no clinical, biochemical, or hematological signs of coagulopathies. During the procedure, he developed hemorrhagic bronchial mucosa syndrome after a bout of uncontrolled severe coughing. This is an extremely rare complication of this procedure. A description of this condition and its mechanism is discussed here.